Pemanfaatan Instagram Dalam Pemasaran Pasar Global - Mohammad Fabilla Arvisha; Endri Listiani (Bandung Conference Series: Communication Management, 2022)
Abstract. This research is entitled Utilization of Instagram in Global Market Marketing (A Case Study of Using Instagram Feeds as a Promotion of Riders and Rules helmet products) Where Riders and Rules conducts promotional events using Instagram feeds because the Instagram market segment has a lot of users. This task is carried out by the Rides and Rules digital marketing team.The purpose of this study is to find out the application of Instagram feeds applied by Riders And Rules to reach the global market, To find out the use of Riders and Rules in utilizing promotional tools in the global market, To find out the reasons for choosing Instagram feeds for product sales from Riders and Rules. This research was conducted in the city of Bandung.In this study using a qualitative case study method with data collection observations, interviews. Key informants in this study were 4 Riders and Rules employees who knew about the promotion program for using Instagram feeds. And 1 Riders and Rules follower who always follows Riders and Rules social media.The researcher chose the Riders and Rules Instagram feed promotion activity to be the subject of research because he wanted to know more about the purpose and design of Riders and Rules by creating a promotional event in the use of Instagram feeds about how Riders and Rules parties with promotional strategies in using social media insatgram. The subject of this research is the promotion of Riders and Rules in promotion using Instagram social media through feeds. Abstrak. Penelitian ini berjudul Pemanfaatan Instagram Dalam Pemasaran Pasar Global (Studi Kasus Penggunaan Feed Instagram sebagai Promosi produk helm Riders and Rules) Dimana Riders and Rules melakukan ajang promosi dalam menggunakan feed instgram adalah karna segment pasar instgram sangat lah banyak pengguna nya. Tugas ini di lakukan oleh team digital marketing Rides and Rules. Tujuan dari penelitian ini untuk mengetahui penerapan feed instgram yang di terapkan oleh Riders And Rules bisa mencapai pasar global ,Untuk mengetahui pemanfaatan Riders and Rules dalam memanfaatkan sarana promosi di pasar global, Untuk mengetahui alasan pemilihan feed instagram untuk penjualan produk dari Riders and Rules. Penelitian ini dilakukan di kota Bandung. Dalam penelitian ini menggunakan metode study kasus kualitatif dengan pengambilan data observasi,wawancara. Key informan dalam penelitian ini adalah dari 4 orang kariyawan Riders and Rules yang mengetahui tentang program promosi penggunan feed instgaram. Dan 1 orang followers Riders and Rules yang selalu mengikuti social media Riders and Rules.Peneliti memlih kegiatan promosi feeds Instagram Riders and Rules untuk menjadi subjek penelitian karna ingin mengatahui lebih jauh tujuan dan rancangan Riders and Rules dengan membuat ajang promosi dalam pengguan feeds instagram tentang bagaimana pihak Riders and Rules dengan strategi promosi dalam menggunakan media soasial insatgram . Subjek penelitian ini adalah kegiatan prosmosi Riders and Rules dalam promosi menggunakan media social Instagram melalui feeds .